Strategi Guru PAI Untuk Meningkatkan Motivasi Belajar Siswa Dalam Mata Pelajaran SKI - Dinda, Wira Restia; Arifmiboy, Arifmiboy (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
Education is the key to improving the state of Indonesia. Begins with motivational encouragement that grows from the students themselves. To create motivation to learn, teachers also need to know what things can support the learning process so that the desired learning goals can be achieved. One of themis with the subject of Islamic Cultural History, many students have been observed and researched who are not interested in studying History, with motivational encouragement, new teachers can change the old habits of passive students into new, active habits so that learning can develop and to achieve curriculum goals that are wanted.